Analýza trhu ryb a mořských produktů v ČR - Šáchová, Lucie; Mlejnková, Lena; Čáp, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
Diploma thesis describes the composition of fish meat and its inventions in the diet, shows the development of global fish production and fish consumption and the development of fish consumption in Czech Republic between 1990-2008. This thesis also examines the current product portfolio and provides an overview of entities operating in the Czech market. Based on the questionnaire provides a forecast of probable future trends and possible developments.
Vedoucí práce: Lena Mlejnková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: cestovní ruch [obor dipl. práce]; diplomové práce; master's theses